Evolution of the thermodynamic properties of a coronal mass ejection in the inner Corona - Sheoran, Jyoti; Pant, Vaibhav; Patel, Ritesh; Banerjee, Dipankar (Frontiers in Astronomy and Space Sciences, 2023)
The thermodynamic evolution of Coronal Mass Ejections (CMEs) in the inner corona (≤ 1.5 R sun ) is not yet completely understood. In this work, we study the evolution of thermodynamic properties of a CME core observed in the inner corona on July 20, 2017, by combining the MLSO/K-Cor white-light and the MLSO/CoMP Fe XIII 10747 Å line spectroscopic data. We also estimate the emission measure weighted temperature (TEM ) of the CME core by applying the Differential Emission Measure (DEM) inversion technique on the SDO/AIA six EUV channels data and compare it with the effective temperature (Teff ) obtained using Fe XIII line width measurements. We find that the Teff and TEM of the CME core show similar variation and remain almost constant as the CME propagates from ∼1.05 to 1.35 R sun . The temperature of the CME core is of the order of million-degree kelvin, indicating that it is not associated with a prominence. Further, we estimate the electron density of this CME core using K-Cor polarized brightness (pB) data and found it decreasing by a factor of ~3.6 as the core evolves. An interesting finding is that the temperature of the CME core remains almost constant despite expected adiabatic cooling due to the expansion of the CME core, which suggests that the CME core plasma must be heated as it propagates. We conclude that the expansion of this CME core behaves more like an isothermal than an adiabatic process.